2013
DOI: 10.3109/10641963.2013.783048
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of (Na,K)-ATPase activity by membrane fatty acid composition: therapeutic implications in human hypertension

Abstract: Oxidative stress (OS) plays a key role in the pathophysiology of essential hypertension and is associated with changes in the cell membrane fatty acid composition and fluidity. As (Na,K)-ATPase is modulated by the surrounding lipid microenvironment, lipid peroxidation could alter the interactions of this enzyme with the membrane components. Thus, modifications in the membrane fatty acid profile will translate into effects on (Na,K)-ATPase activity. Accordingly, a decrease in this enzyme activity has been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 62 publications
2
15
0
1
Order By: Relevance
“…The comparison of linear regression curves by one-way ANOVA showed significant differences between the slopes (p ≤ 0.0001). These results are in agreement with previous studies, showing that the unsaturation index (UI) of membrane phospholipids is one of the major factors influencing membrane fluidity [21][22][23] In agreement with previous studies [34], fatty acid analysis of HMEC, enriched with EPA and DHA, revealed an increase of the ratio between saturated and polyunsaturated fatty acids, and a consequent increase in the concentration of double bonds in membrane phospholipids (unsaturation index, UI). As expected and depicted in Figure 2C, at each dose of n-3 LC-PUFA added to cell culture medium, DHA (six double bonds) determined a greater increase of UI than EPA (five double bonds).…”
Section: Effects Of N-3 Lc-pufa Incorporation On Membrane Fluidity Insupporting
confidence: 93%
“…The comparison of linear regression curves by one-way ANOVA showed significant differences between the slopes (p ≤ 0.0001). These results are in agreement with previous studies, showing that the unsaturation index (UI) of membrane phospholipids is one of the major factors influencing membrane fluidity [21][22][23] In agreement with previous studies [34], fatty acid analysis of HMEC, enriched with EPA and DHA, revealed an increase of the ratio between saturated and polyunsaturated fatty acids, and a consequent increase in the concentration of double bonds in membrane phospholipids (unsaturation index, UI). As expected and depicted in Figure 2C, at each dose of n-3 LC-PUFA added to cell culture medium, DHA (six double bonds) determined a greater increase of UI than EPA (five double bonds).…”
Section: Effects Of N-3 Lc-pufa Incorporation On Membrane Fluidity Insupporting
confidence: 93%
“…Regarding our second question, and based on the results of binomial logistic regression analysis, the GSSG/GSH ratio was the most significant predictive factor among OS parameters for the development of BRONJ. This ratio can be used to measure redox status , and some authors have confirmed that it is an indicator of systemic redox status . The transformation of GSH into GSSG involves the transformation of a hydrogen peroxide molecule into a water molecule .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in the groups receiving chronic HFD, both stressed or not, the activity of Na + ,K + -ATPase was similar to the control group. It is known that modifications in the membrane fatty acid profile will translate into effects in Na + ,K + -ATPase activity (Rodrigo et al, 2014). It is possible that a chronic administration of a HFD could be causing some alteration in membrane fluidity, changing the activity of this pump.…”
Section: Discussionmentioning
confidence: 99%